![](http://hiphotos.baidu.com/zhidao/pic/item/7e3e6709c93d70cffb3963bcfbdcd100bba12b44.jpg)
證明:由已知得△ABC≌△AB1C1,
所以∠BAC=∠B1AC1,∠B1AB=∠C1AC,
因?yàn)锳C1=AC,
所以∠AC1C=∠ACC1,
因?yàn)椤螩1AC+∠AC1C+∠ACC1=180°,
所以∠C1AC=180°-2∠ACC1,
同理,在△ABC中,
因?yàn)锽A=BC,
所以∠ABC=180°-2∠ACC1,
所以∠ABC=∠C1AC=∠B1AB,
所以AB1∥BC.
(2)如圖1,∠C=60°時,AB1∥BC.
(3)如圖,當(dāng)∠C<60°時,(1)、(2)中的結(jié)論還成立.
證明:顯然△ABC≌△AB1C1,
所以∠BAC=∠B1AC1,
所以∠B1AB=∠C1AC,
![](http://hiphotos.baidu.com/zhidao/pic/item/9e3df8dcd100baa108ef8e0a4410b912c9fc2e44.jpg)
因?yàn)锳C1=AC,
所以∠AC1C=∠ACC1,
因?yàn)椤螩1AC+∠AC1C+∠ACC1=180°,
所以∠C1AC=180°-2∠ACC1,
同理,在△ABC中,
因?yàn)锽A=BC,
所以∠ABC=180°-2∠ACC1,
所以∠ABC=∠C1AC=∠B1AB,
所以AB1∥BC.